LGR4 and LGR5 Regulate Hair Cell Differentiation in the Sensory Epithelium of the Developing Mouse Cochlea - Żak, Magdalena; van Oort, Thijs; Hendriksen, Ferry G.; Garcia, Marie-Isabelle; Vassart, Gilbert; Grolman, Wilko (Frontiers in Cellular Neuroscience, 2016)
In the developing cochlea, Wnt/β-catenin signaling positively regulates the proliferation of precursors and promotes the formation of hair cells by up-regulating Atoh1 expression. Not much, however, is known about the regulation of Wnt/β-catenin activity in the cochlea. In multiple tissues, the activity of Wnt/β-catenin signaling is modulated by an interaction between LGR receptors and their ligands from the R-spondin family. The deficiency in Lgr4 and Lgr5 genes leads to developmental malformations and lethality. Using the Lgr5 knock-in mouse line we show that loss of LGR5 function increases Wnt/β-catenin activity in the embryonic cochlea, resulting in a mild overproduction of inner and outer hair cells. Supernumerary hair cells are likely formed due to an up-regulation of the "pro-hair cell" transcription factors Atoh1, Nhlh1, and Pou4f3. Using a hypomorphic Lgr4 mouse model we showed a mild overproduction of outer hair cells in the heterozygous and homozygous Lgr4 mice. The loss of LGR4 function prolonged the proliferation in the mid-basal turn of E13 cochleae, causing an increase in the number of SOX2-positive precursor cells within the pro-sensory domain. The premature differentiation of hair cells progressed in a medial to lateral gradient in Lgr4 deficient embryos. No significant up-regulation of Atoh1 was observed following Lgr4 deletion. Altogether, our findings suggest that LGR4 and LGR5 play an important role in the regulation of hair cell differentiation in the embryonic cochlea.